MICROPROPAGATION FOR THE CONSERVATION OF RARE AND ENDANGERED MALUS NIEDZWETZKYANA - Nurtaza , A.S.; Magzumova , G.K.; Yessimseitova , A.K.; Dyussembekova , D.A.; Baktybay , B.; Turganbayeva , A.K.; Kakimzhanova , A.A. (Eurasian Journal of Applied Biotechnology, 2019)
The conservation of biological diversity is one of the most important tasks at present given the strong association of biodiversity with food security and improving nutrition. Currently, 387 plant species are listed in the Red Book of Kazakhstan, including the rare, endemic, and endangered species Malus niedzwetzkyana, which is also included on the International Red List. Biotechnology methods are currently widely applied to preserve such rare plant species, which allows for the long-term preservation of genetic material, enabling their large-scale reproduction and propagation. One of the most effective methods for this purpose is microclonal propagation, which is similar to the vegetative method of reproduction except that the entire process proceeds with an in vitro culture system. The resulting clones are healthy and genetically stable. In this study, we optimized the microclonal propagation technique for Malus niedzwetzkyana. Axillary buds of annual shoots were used as the initial material. The mode of sterilization of the axillary buds, composition of the nutrient medium for establishment of in vitro culture, and the multiplication and rooting of microshoots were optimized. The data obtained provide an essential resource for sustaining the reproduction and propagation of this rare and endangered species of apple trees.